2018
DOI: 10.1111/ggi.13492
|View full text |Cite
|
Sign up to set email alerts
|

Application of smart bracelet to monitor frailty‐related gait parameters of older Chinese adults: A preliminary study

Abstract: The present study suggested that the decline in gait parameters as a result of frailty could be detected by the smart bracelet sensor. Geriatr Gerontol Int 2018; 18: 1366-1371.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…In this study, we aimed to improve detection of frailty-related neuromuscular deficits based on gait performance parameters derived from unsupervised DPA. Previous studies have used trunk motion data from supervised in-lab gait tests to characterize sensorimotor gait performance among frail elders including gait variability, asymmetry, initiation, and irregularity (10,11,(13)(14)(15)(16)(17). We hypothesized that using more robust measures of unsupervised DPA gait performance (instead of number of steps) it would be possible to distinguish between non-frail and pre-frail older adults.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we aimed to improve detection of frailty-related neuromuscular deficits based on gait performance parameters derived from unsupervised DPA. Previous studies have used trunk motion data from supervised in-lab gait tests to characterize sensorimotor gait performance among frail elders including gait variability, asymmetry, initiation, and irregularity (10,11,(13)(14)(15)(16)(17). We hypothesized that using more robust measures of unsupervised DPA gait performance (instead of number of steps) it would be possible to distinguish between non-frail and pre-frail older adults.…”
Section: Introductionmentioning
confidence: 99%
“…Gait Irregularity: Results from supervised gait studies showed that irregularity measures can describe predictability of walking cycles, which can be influenced by both neurological and neuromuscular diseases (46)(47)(48)(49). Further, within in-lab settings, it has been demonstrated that gait irregularity can differ between non-frail and pre-frail older adults (21). We used Sample Entropy (SampEn) assessment defined as equation (2), where was defined as the number of matches in the filtered acceleration signal length (distance function smaller than tolerance ) and as the number of matches of length ( ) (50)(51)(52)(53)(54).…”
Section: Continuous Walking Boutsmentioning
confidence: 99%
“…In this study, we aimed to improve detection of frailty-related neuromuscular deficits based on gait performance parameters derived from unsupervised DPA. Previous studies have used trunk motion data from supervised in-lab gait tests to characterize sensorimotor gait performance among frail elders including gait variability, asymmetry, initiation, and irregularity (11,12,(18)(19)(20)(21)(22). We hypothesized that using more robust measures of unsupervised DPA gait performance such as gait variability, asymmetry and irregularity (instead of number of steps) it would be possible to distinguish between non-frail and pre-frail/frail older adults.…”
mentioning
confidence: 99%
“…Furthermore, when users disclose money information to human beings, they are usually seeking financial support or investment advice from others; users might not believe that IoT-CAs currently have the social capital or intelligence to provide financial support and advice. However, in terms of users' self-disclosure of body information, various IoT devices have been recently developed and applied for health care and monitoring [56,57]. Users' body information is being collected and effectively used for the detection of personal conditions and future disease prevention.…”
Section: Self-disclosure Of Information To Iot-casmentioning
confidence: 99%